2023
DOI: 10.3390/jcm12216950
|View full text |Cite
|
Sign up to set email alerts
|

Initial Learning Curve for Robot-Assisted Total Knee Arthroplasty in a Dedicated Orthopedics Center

Serban Dragosloveanu,
Mihnea-Alexandru Petre,
Bogdan Sorin Capitanu
et al.

Abstract: Background and objectives: Our study aimed to assess the learning curve for robot-assisted (RA) total knee arthroplasty (TKA) in our hospital, compare operative times between RA-TKAs and manual TKAs, and assess the early complications rate between the two approaches. Methods: We included 39 patients who underwent RA-TKA and 45 control patients subjected to manual TKA in the same period and operated on by the same surgical staff. We collected demographic and patient-related data to assess potential differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…These main factors were also identified in our patient lot, either alone or combined; however, the analysis of the clinical parameters and risk factors was outside the scope of this paper. Nevertheless, while significant progress in rTKA indications, surgical planning and approach, robotic-assisted surgical options, management, and follow-up of patients has been recorded throughout the last 20 years, the definitive role and contribution of these improvements to primary TKA failure remain to be established [69][70][71][72][73][74][75][76][77].…”
Section: Discussionmentioning
confidence: 99%
“…These main factors were also identified in our patient lot, either alone or combined; however, the analysis of the clinical parameters and risk factors was outside the scope of this paper. Nevertheless, while significant progress in rTKA indications, surgical planning and approach, robotic-assisted surgical options, management, and follow-up of patients has been recorded throughout the last 20 years, the definitive role and contribution of these improvements to primary TKA failure remain to be established [69][70][71][72][73][74][75][76][77].…”
Section: Discussionmentioning
confidence: 99%
“…Adequate training is required for all new systems and technologies. Studies have shown that the learning curve for RATKA ranges from 7 to 80 cases [20][21][22][23]. However, the majority of studies have revealed that the learning curve of RATKA in terms of surgical proficiency and surgeons' confidence levels is relatively short, ranging from 7 to 11 cases [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…If significant bone defects are present due to trauma or associated pathologies, vertebroplasty can be performed using adequate medical-grade compounds [66][67][68]. Robotic surgery can also be considered as it is emerging as a safe, reliable technique and is increasingly applied in all surgical areas [69][70][71].…”
Section: Discectomy and Fusionmentioning
confidence: 99%